Nano Ca–Mg–Zn ferrites as tuneable photocatalyst for UV light-induced degradation of rhodamine B dye and antimicrobial behavior for water purification. Issue 8 (15th April 2023) - Kumari, Sonam; Dhanda, Neetu; Thakur, Atul; Gupta, Vaishali; Singh, Satyendra; Kumar, Rakesh; Hameed, Saif; Thakur, Preeti
Abstract: We report the synthesis of Ca-doped Mg–Zn ferrite Mg0.4 Zn(0.6-x) Cax Fe2 O4 nanomaterials with x = 0, 0.1, 0.2, 0.3, 0.4, 0.5, and 0.6 through citrate precursor approach and their structural, morphological, optical, photocatalytic, and antimicrobial properties were systematically studied. The prepared nanoferrites's cubic spinel structure with an average crystallite size of 15–38 nm was evaluated by the XRD examination. The spherical morphology of these ferrite nanoparticles was seen from scanning electron microscopy (SEM). The observed bands at 560 cm −1 and 406 cm −1 in the FTIR spectra confirmed the spinel structure of the synthesized nanoferrite. The optical study confirmed an optical band gap of 1.60 eV–1.86 eV. The photocatalysis was done for the degradation of rhodamine B dye solution under UV light. All the synthesized nano ferrites displayed a promising antimicrobial potential upon Candida albicans fungi. Mg0.4 Zn0.1 Ca0.5 Fe2 O4 nanoparticles have a better photocatalytic response (99.5%) for the degradation of rhodamine B dye and show superior antimicrobial activity (96.1%) for the inhibition of Candida albicans fungi.